High-Dose Shilajit Enhances Xenograft-Mediated Bone Regeneration in a Rat Tibial Defect Model: An In Vivo Experimental Study - Guler, Ridvan; Ozden, Ersin; Asir, Firat; Gulsun, Belgin (Mdpi, 2025)
Shilajit, a natural herbo-mineral compound with potent antioxidant, anti-inflammatory, and osteogenic properties, has been traditionally used to promote tissue repair. However, limited experimental data exist on its localized application in bone regeneration. This study aimed to evaluate the combined effect of Shilajit and bovine-derived xenograft on bone healing in a rat tibial defect model. Twenty-eight male Sprague-Dawley rats were randomly assigned to four groups (n = 7): Control (defect left to heal spontaneously), Graft-only, Graft + Shilajit 150 mg/kg, and Graft + Shilajit 250 mg/kg. Standardized 3 mm tibial defects were created and filled with xenograft in all groups except the Control. Shilajit was administered intraperitoneally on days 0-3 postoperatively. After 4 weeks, serum total oxidant status (TOS), total antioxidant status (TAS), and TNF-alpha levels were measured. Tibial specimens underwent histopathological, histomorphometric, and TNF-alpha immunohistochemical analysis. High-dose Shilajit significantly increased TAS and reduced TOS compared with the Control and Graft-only groups (p < 0.001). Median TNF-alpha concentrations decreased in a dose-dependent manner, with the lowest values in the high-dose group (15.7 [14.3-17.1] pg/mL, p < 0.001). Histomorphometry revealed the highest new bone area percentage (78.1% [74.9-81.2]) and lowest fibrous tissue content (9.8% [8.1-11.6]) in the high-dose group. Immunohistochemistry confirmed marked suppression of TNF-alpha expression in Shilajit-treated groups, particularly at high doses. The combination of Shilajit and bovine-derived xenograft significantly enhanced bone regeneration in a dose-dependent manner, likely through antioxidative, anti-inflammatory, and osteogenic mechanisms. These findings suggest that Shilajit may serve as a promising adjunct in bone grafting procedures.
Keywords: Shilajit; xenograft; bone regeneration; oxidative stress; TNF-alpha; histology; immunohistochemistry